2020
DOI: 10.1186/s13104-020-05195-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of blue dishware versus white dishware on food intake and eating challenges among residents living with dementia: a crossover trial

Abstract: Objective Residents living with dementia (RLWD) often experience changes in their visual perception, which could reduce food intake. Inadequate food intake is known to cause malnutrition, which increases the risk of hospitalization, morbidity, and mortality. This study evaluated the effectiveness of using blue dishware compared to white dishware to improve food intake and mitigate eating challenges among 18 RLWD (mean age 84.6 ± 7.9 years, 72.2% female). Results A withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Moreover, implementing high-frequency food services containing protein-rich meals and attractive meal presentation led to improved protein intake at mealtimes during the day [31]. A recent study was conducted by Donnelly et al [74] to compare the efficacy of blue versus white dishware in increasing food consumption and mitigating eating challenges among dementia residents. This systematic review concluded that the factors affecting food intake among residents living with dementia were complex.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, implementing high-frequency food services containing protein-rich meals and attractive meal presentation led to improved protein intake at mealtimes during the day [31]. A recent study was conducted by Donnelly et al [74] to compare the efficacy of blue versus white dishware in increasing food consumption and mitigating eating challenges among dementia residents. This systematic review concluded that the factors affecting food intake among residents living with dementia were complex.…”
Section: Discussionmentioning
confidence: 99%